Manajemen Kurikulum Dan Pembelajaran Di MA Sumbersari Tuban - Ahmad Agil Siroj; Munirul Abidin; Tatang Aulia Rahman (Institut Agama Islam Al-Hikmah Tuban, 2023)
This study aims to examine: (1). Curriculum and learning management, (2).Curriculum planning in the school, (3). Organizing the curriculum in the school, (4).Implementation of the curriculum in the school. This research uses descriptivequalitative research method. Data research were collected through interviews,observations, document studies. Further data are analyzed, reduced, verified thendrawn conclusions. The results of this study show that: First, curriculum andlearning management at Sumbersari Tuban School begins with the planning, organizing,and implementation of the curriculum. Second, Curriculum Planning Sumbersari School has been running with a structured but still needs to be done alignment ofplans that have been made in order to be planned all that has been set at planningmeetings conducted routinely at the beginning of the semester. Third, the organizingof curriculum at Sumbersari Tuban School covers two things: structural and academic.Structurally a curriculum organizing system under the command of the Director(Principal). While the academic organization of the curriculum is developed in theform of an organization that is curriculum based on separate subjects (SaparatedSubject Curriculum). Fourth, the implementation of curriculum at Sumbersari Tuban Schoolis divided into two levels namely the implementation of school and class curriculum.In the implementation of school-level curricula undertaken by the principal is stillless than the maximum because of the lack of existence of the principal. While for the implementation of the class-level curriculum implemented by the teacher is maximal enough with evidence in the learning process has been following the times.Keywords: Management, Curriculum, Learning